Acute and chronic Q fever national surveillance – United States, 2008–2017. (8th October 2021) - Cherry, Cara C.; Nichols Heitman, Kristen; Bestul, Nicolette C.; Kersh, Gilbert J.
Abstract: Q fever is a zoonotic disease caused by the bacterium Coxiella burnetii and can manifest in an acute or chronic form. Many persons with acute Q fever are asymptomatic, but some develop a febrile illness, pneumonia or hepatitis. Chronic infections are rare and occur in less than 5% of persons exposed. Forms of chronic Q fever include endocarditis, infection of vascular grafts or aneurysms, osteomyelitis and osteoarthritis. Acute and chronic Q fever are nationally notifiable diseases, and presented here are the incidence, demographics and distribution of acute and chronic Q fever in the United States during 2008–2017. We summarized passive surveillance data from the Centers for Disease Control and Prevention's (CDC) National Notifiable Diseases Surveillance System (NNDSS) and supplemental case report forms (CRFs). Health departments reported 1, 109 cases of acute Q fever and 272 chronic Q fever cases to NNDSS during this period. The 10‐year average annual incidence for acute Q fever was 0.36 cases per million persons, and the average annual incidence for chronic Q fever was 0.09. Males accounted for nearly 75% of both acute and chronic Q fever cases. Average annual incidence was highest among persons aged 60–69 years for both acute and chronic Q fever (0.70 cases per million persons and 0.25, respectively). As reported through CRFs, many Q fever cases did not have a known exposure to C. burnetii ; 60% ( n = 380) of acute Q fever cases did not report exposure to animals in the 2 months before symptom onset. Almost 90% ( n = 558) did not report exposure to unpasteurized milk. Only 40% ( n = 247) of persons with reported Q fever were employed in high‐risk occupations. Even though Q fever is a rare disease in the United States, incidence doubled from 2008 to 2017.